Clonality analysis of combined Brenner and mucinous tumours of the ovary reveals their monoclonal origin. Issue 2 (23rd July 2015) - Wang, Yihong; Wu, Ren‐chin; Shwartz, Lauren Ende; Haley, Lisa; Lin, Ming‐tse; Shih, Ie‐ming; Kurman, Robert J
Abstract The derivation of ovarian intestinal‐type mucinous tumours is not well established. Some are derived from teratomas but the origin of the majority is not clear. It has been recently proposed that the non‐germ cell group may be derived from Brenner tumours, as the association of a mucinous tumour with a Brenner tumour is frequently observed. In order to explore the histogenesis of these neoplasms, we undertook a clonality analysis of the two components of ten combined Brenner and mucinous tumours using a human androgen receptor gene (HUMARA) assay. All eight informative cases of ten showed a concordant X‐chromosome inactivation pattern between the two tumour components, indicative of a shared clonal origin (p = 0.0039). Microsatellite genotyping in five of the combined tumours displayed an identical heterozygous pattern with paired Fallopian tube tissue, indicative of a somatic cell origin. In addition, paired box protein 8, a highly sensitive Müllerian epithelial marker, was not detected by immunohistochemistry in either tumour component in any of the ten tumours, suggesting that this subset of mucinous tumours does not originate from Müllerian‐derived epithelium. In conclusion, this study demonstrates that in combined mucinous and Brenner tumours, there is a shared clonal relationship between the two different tumour components and suggests that some pure mucinous tumours may develop from a Brenner tumour in which the Brenner tumour component becomes compressed and obliterated by an expanding mucinous neoplasm. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.